Суперіонні провідники та їх використання в сучасних хімічних джерелах струму - Рясна, А. К.; Коваленко, О. М. (ХНУРЕ, 2025)
The work is devoted to the study of the possibility of using superionic compounds in the manufacture of energy storage systems. With the rapid progress in the field of alternative sources of energy, it becomes necessary to develop appropriate efficient devices for its storage. Solid electrolytes can become an alternative to conventional liquid electrolytes. The paper compares the main types of solid electrolytes from the point of view of their properties. The advantages of solid electrolytes for creating safe, flexible, durable energy storage devices are also considered.
Keywords: суперіонні провідники; хімічне джерело струму